Zimbabwe Climate Smart Agriculture Investment Plan - World Bank (World Bank, Washington, DC, 2019)
This report presents a climate smart investment plan (CSAIP) for Zimbabwe’s agricultural sector. The agricultural sector plays a critical role in the Zimbabwean economy, serving as a source of livelihood for approximately 70 percent of the population and contributing 15 to 20 percent to gross domestic product (GDP). In response, the Government of Zimbabwe, with the assistance of the World Bank, is supporting the development of this CSAIP. This CSAIP identifies and prioritizes packages of CSA investments and policy actions that will support improvement across three key CSA pillars, namely the achievement of a more productive, resilient, and low-emissions agricultural sector. It provides guidance on implementation mechanisms for these CSA interventions, discussing details such as investment costs and supporting institutional arrangements. It seeks to align goals and objectives across Zimbabwe’s existing agricultural policies and climate change strategies, which will contribute to the achievement of the country’s vision 2030, and the nationally determined contributions (NDCs), among others. Additionally, this CSAIP is intended to serve as an input to developing a new, climate resilient Zimbabwe AIP for the future. This report is structured as follows: chapter one gives introduction; chapter two presents relevant background information on climate change and Zimbabwe’s agricultural sector; chapter three describes the methodology of how the general CSAIP approach was applied to the specific case of Zimbabwe’s agricultural sector; chapter four presents some analytic results highlighting the challenges that will be faced by Zimbabwe’s agricultural sector under an uncertain future and provides evidence in support of the role of CSA in addressing these vulnerabilities; chapter five presents results of the process of producing prioritized packages of CSA investments and takes a detailed look at each of these recommended packages; and chapter six concludes with a summary, a set of recommendations and next steps.